Preparation of Sol-Enhanced Ni–P–Al2O3 Nanocomposite Coating by Electrodeposition. (18th May 2020) - Li, Yongfeng; Zhang, Kun; Zhang, Mingming; Zhang, Yaqi; Wu, Tingting; Zhao, Hongyuan; Su, Jianxiu; Wang, Zhankui; Wang, Junfeng
Abstract : A Ni–P–(sol)Al2 O3 coating was prepared on the surface of Q235 steel by direct-current electrodeposition. This method was combined with sol-gel and electrodeposition technique, instead of the traditional nanopowder dispersion, to prepare highly dispersible oxide nanoparticle-reinforced composites. The effects of temperature, pH value, and current density and Al2 O3 sol on the hardness of composite coating were investigated. The coating surface morphology and structure were characterized by scanning electron microscopy and energy dispersive spectroscopy, respectively. The corrosion resistance of coatings in the presence of intermediate layers was evaluated by electrochemical measurement in 3.5% NaCl solution by open-circuit potential measurement at room temperature. The hardness and wear resistance of the coating were measured by a microindentation instrument and friction wear machine, respectively. The results showed that Al2 O3 sol can effectively improve Ni–P alloy coating structure and refine grain. When the bath temperature was 55°C, the pH value was 4.5, the amount of sol was 80 mL/L, the current density was 1 A/dm 2, and the hardness of the nanosol coating was 569 HV. Compared with Ni–P, the friction coefficient increases slightly, but the wear rate was only 1.768 × 10 − 6 g · m − 1 . The corrosion resistance was also better than that of Ni–P coating.